Aktivitas antiinflamasi ekstrak etanol tanaman patah tulang (euphorbia tirucalli l.) - Mamarimbing, Merlyn Santa; I Gusti Ngurah Agung Dewantara Putra; Eka Indra Setyawan (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Inflammation is a normal protective response to tissue injury caused by physical trauma, damaging chemical substances or microbiological substances. This study aimed to determine the potential anti-inflammatory activity of the ethanolic extract of the pencil cactus plant. The method used in this study was a literature study with a descriptive qualitative research type with a systematic literature review. The results showed that the ethanolic extract of the pencil cactus plant has anti-inflammatory activity by significantly reducing edema in the feet of rats.